Latent transitions across perceived parental marital conflict and family cohesion profiles in high school students - Gao, Tingting; Liang, Leilei; Li, Muzi; Su, Yingying; Mei, Songli; Zhou, Chengchao; Meng, Xiangfei (Frontiers in Psychology, 2022)
This study aimed to explore the latent profiles across perceived parental marital conflict and family cohesion, as well as the transition patterns within-person and within-sample profiles over time. We conducted a 1-year follow-up study with a sample of first-year high school students from China. A total of 453 participants were included in the present analysis. We identified the following three latent profiles: high parental conflict and poor family cohesion profile, moderate parental conflict and family cohesion profile, and low parental conflict and good family cohesion profile. Female students and those who not lived with parents together were more likely to perceive more parental marital conflict and less cohesion in the family. The majority of students with high transition probability remained in the same profiles over time. The counts of latent transition pattern also demonstrated that students remaining in the primary profile over time accounted for the large proportion. The present study advances empirical bases for confirming the family system theory’s notion that the family is not static, but dynamic. Findings provide the optimal timing of interventions toward healthy transition.